2017
DOI: 10.1080/23311886.2017.1368858
|View full text |Cite
|
Sign up to set email alerts
|

The physiology of adolescent sexual behaviour: A systematic review

Abstract: Objectives: To examine physiological influences of adolescent sexual behaviour, including associated psychosocial factors. Methods: Systematic review. Results: Thirteen studies met the inclusion criteria relating to adolescents, physiology and sexual behaviour. We excluded studies relating to abnormal development. Findings highlighted hormonal and gender differences. Females appear to be more influenced by psychosocial aspects, including the effects of peers, than males. Males may be more inclined to engage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 35 publications
(42 reference statements)
0
58
2
7
Order By: Relevance
“…49 Furthermore, sexual behaviour in adolescents have changed and must be reconsidered when evaluating adolescents with LUTD. 50 In a retrospective study, adults with OAB (mean age, 53.4 years) reported higher rates of childhood sexual trauma than controls (29.4% vs 6.7%). 51 A large community-based epidemiologic study showed a strong association between urinary frequency, urgency and nocturia and abuse.…”
Section: Psychological Symptoms/disorders and Stressors Cause Lutdmentioning
confidence: 97%
See 1 more Smart Citation
“…49 Furthermore, sexual behaviour in adolescents have changed and must be reconsidered when evaluating adolescents with LUTD. 50 In a retrospective study, adults with OAB (mean age, 53.4 years) reported higher rates of childhood sexual trauma than controls (29.4% vs 6.7%). 51 A large community-based epidemiologic study showed a strong association between urinary frequency, urgency and nocturia and abuse.…”
Section: Psychological Symptoms/disorders and Stressors Cause Lutdmentioning
confidence: 97%
“…The negative effects of some of these substances on lower urinary tract function are reported . Furthermore, sexual behaviour in adolescents have changed and must be reconsidered when evaluating adolescents with LUTD …”
Section: Models Of Aetiologymentioning
confidence: 99%
“…Another associated problem is substance abuse, which has increased markedly between 1990 and 2010 and carries negative effects on LUT function . Sexual behavior in adolescents has an effect on LUTD, as well …”
Section: Transition Of Childhood DV Into Adulthoodmentioning
confidence: 99%
“…56 Sexual behavior in adolescents has an effect on LUTD, as well. 57 In the transitional care of DV, challenges are present in the methods of evaluation and management. Renal and bladder ultrasounds are useful and standard assessment in pediatric and adult patients.…”
Section: S85mentioning
confidence: 99%
“…Young adulthood is a particularly vulnerable time in relation to burgeoning independence, developing sexuality, and first forays into intimate relationship formation [7, 8]. While many child protection processes highlight the risks to younger children, there appears to have been less emphasis on older children [9].…”
Section: Introductionmentioning
confidence: 99%